An Integrated Approach to Improve the Knowledge of Ostreid Herpesvirus Type 1 and the Comprehension of Mortality Events in the Pacific Oyster Crassostrea Gigas - Burioli, Erika Astrid Virginie <1977> (Alma Mater Studiorum - Università di Bologna, 2017)
In a period of expansion of oysters farming in Italy, the present work aimed to contribute to this challenge approaching several important aspects connected with oyster health management. Firstly, we evidenced the presence of natural populations of C. gigas along the Italian coasts and showed differences in the distribution and density population between Adriatic and Tyrrhenian Sea. The presence of OsHV-1 infecting these wild populations was detected in all the Adriatic beds, demonstrating high diversity of genotypes, and showing that these individuals may play a role as reservoir of infection in farmed stocks allocated in the same sites. No other potential reservoir hosts have been evidenced during the investigation conducted in other mollusc species. The obtainment of the complete sequence of OsHV-1 µVar genome represents a significant goal reached during the present work. In particular, this result will permit the exploration of virulence factor in future, a better use of transcriptomics, and the development of new specific diagnostic tools.The complete comprehension of the mechanisms at the origin of the mortality events, observed during the two-year survey, is arduous but the study allowed to observe and obtain highly useful information on oyster mortalities and associated pathogens, specifically in the Italian context. In particular, the impact of V. aestuarianus seems to be relevant in some areas.A potential new pathogen for adult oysters, a Tenacibaculum strain, has been decribed.